Neuroscience and Criminal Law: Credibility of the witness in light of the advances on the nervous system - Herrera Camareno, Danny (2020)
The purpose of this article is to study the value of testimony as mean of evidence, especially its credibility, confronting it with advances in the nervous system. With this purpose, a brief review of the concepts of Neuroscience and Neurolaw will be made, to give a necessary scientific context, to later analyze some elements that must be considered when evaluating a testimony.